"I Have Nothing Else to Give": A Qualitative Exploration of Emergency Medicine Residents' Perceptions of Burnout. Issue 4 (8th August 2021) - Jain, Aarti; Tabatabai, Ramin; Vo, Anne; Riddell, Jeffrey
Abstract: Phenomenon: : Resident physicians experience high degrees of burnout. Medical educators are tasked with implementing burnout interventions, however they possess an incomplete understanding of residents' lived experiences with this phenomenon. Attempts to understand burnout using quantitative methods may insufficiently capture the complexities of resident burnout and limit our ability to implement meaningful specialty-specific interventions. Qualitative studies examining how residents conceptualize burnout have been briefly examined in other specialties, however the specific stressors that characterize emergency medicine training may lead residents to experience burnout differently. This study used qualitative methodology to explore emergency medicine trainees' perceptions of the complex phenomenon of burnout during their residency training years. Approach: In order to evaluate a novel wellness intervention at their emergency medicine residency program, the authors conducted four semi-structured focus groups with residents and recent alumni from May 2018 to August 2018. After the focus groups concluded, the authors noted that they lacked an insightful understanding of their residents' own experiences with physician burnout. Thus, they performed a secondary analysis of data initially gathered for the curricular evaluation. They followed a reflexive thematic analysis approach, analyzing all focus group transcripts in an iterative manner, discussing and refining codes, and developing thematic categories. Findings: Residents described individual-level manifestations of burnout in their day-to-day lives, a calloused view of patient suffering in the clinical environment, and a fatalistic view toward burnout during their training. They experienced a pervasive negativity, emotional fragility, and neglect of self that bled into their social environments. Clinically, burnout contributed to the erosion of the therapeutic physician-patient relationship. Residents perceived burnout as an inevitable and necessary element of their residency training years. Insights: Residents' lived experiences with burnout include nonclinical manifestations that challenge existing frameworks suggesting that burnout is restricted to the work domain. Burnout interventions in emergency medicine training programs may be more effective if educators inculcate habitual practices of self-monitoring in trainees and explicitly set resident expectations of patient acuity in the clinical environment. Supplemental data for this article is available online at https://doi.org/10.1080/10401334.2021.1875833 .